Regional Government Policy on Parking Management in Educational Environments in Cilegon City - Zainal Muttaqin; Apud Apud; Uyu Muawwanah (International Journal of Nusantara Islam, 2026)
This study analyzes the Cilegon City regional government's policy on parking management in educational settings through library research. This study examines 40 journal articles and 6 reference books published between 2020 and 2025. This article employs a descriptive qualitative literature review. Data were collected from various academic sources, including scientific journals, books, research reports, education policy documents, regional regulations, and mayoral/regent regulations relevant to local government policy on parking management in educational settings. These sources were systematically analyzed to identify concepts, theories, best practices, and challenges in implementing local government parking management policies in educational settings. Content analysis was conducted to map the key dimensions of local government policy, effective implementation strategies, and success factors and obstacles that influence the effectiveness of local government policy on parking management in educational settings.